Analysis of The Main Character Ava Alessandra in Ika Natassa’s Novel Heartbreak Motel - Amanda Putri Auliya; Sagito Puan Agustio (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
Heartbreak Motel, a romantic drama written by Ika Natassa, follows the emotional journey of Ava Alessandra, an actress dedicated to embodying every character she portrays. Ava immerses herself in various acting techniques and confronts a wide range of emotions experienced by her roles. This analysis delves into the painful experiences faced by the protagonist, examined through the lens of Sigmund Freud’s psychoanalytic theory. Freud’s model explores the dynamic interactions between the id, ego, and superego three elements that shape the human psyche, each influenced by different factors, including traumatic experiences. The purpose of this study is to analyze how the protagonist’s id, ego, and superego interact and manifest through defense mechanisms in response to trauma. A qualitative approach with a descriptive-analytical method was employed. Data were gathered in the form of narrative excerpts that directly support the study's objectives. The findings reveal that the protagonist’s traumatic experiences significantly influence the function of the id, ego, and superego, particularly through the defense mechanisms of repression, sublimation, and introjection. The study also highlights the impact of trauma on the character’s psychological development and her social interactions, offering insights into how fictional experiences reflect real-life psychological struggles.